Les Occlusions Intestinales Par Nœud Ileo-Sigmoïdien : Aspects Diagnostiques, Thérapeutiques Et Pronostiques - L., James Didier.; MS., Chaibou; S., Adama.; K., Idé; MB., Abdoulaye; H., Daddy.; O., Adakal.; H., Adamou; MI., Marouf; T., Sidibe.; et al. (European Scientific Journal, ESJ, 2017)
Introduction: Ileosigmoid knot (ISK), also known as compound volvulus or double volvulus, is a rare disease and affects mostly male subjects in their fourth decade. Delayed diagnosis often leads to complications with a high incidence of digestive necrosis. Materials and methods: This was a 10-year retrospective, descriptive and analytical study from 1 January 2007 to 31 December 2016, which covered all patients operated emergently for ISK in the surgical and surgical specialty departments at the Niamey National Hospital (NNH). Results: The series involved 8 cases of ISK, representing 0.82% of intestinal obstructions. There were 7 men and 1 woman. The average age of patients was 44.33 years with extremes ranging from 25 to 60 years. The main clinical signs were: abdominal pain (100%), inability to pass gas and stool (100%), vomiting (87.5%) and abdominal meteorism (87.5%). Four patients (50%) had a clear obstructive syndrome and the other 4 patients (50%) had associated signs of peritoneal irritation. Paraclinical diagnosis was difficult because of atypical clinico-radiological signs, but in all cases an abdominal x-ray was performed and showed a double loop of dilated sigmoid shadow in 87.5% of the cases. Laparotomy was the first approach used in all patients and led to a 50% necrosis rate. Hartmann’s colectomy and ideal colectomy were used in identical proportions, with 50% each. Ideal colectomy was characterized by a morbidity rate of 50% and a mortality rate of 25% compared to 0% for Hartmann’s procedure. The overall morbidity was 25% and the overall mortality was 12.5%. The average hospital stay was 65.87 days (range 17 to 128 days). The average time before reestablishment of digestive continuity was 50.37 days (range 31-128 days). Conclusion: Ileosigmoid knot is a rare condition at Niamey national hospital where the diagnostic approach is similar to that of occlusions in general, but remains difficult due to its uncommonness and atypical clinico-radiological signs. Necrosis rates and postoperative complications remain high.